Documenting and disseminating agricultural indigenous knowledge for sustainable food security in Uganda - Haumba, Eric Nelson; Kaddu, Sarah (University of Dar es Salaam Library Journal, 2017)
There is a wealth of agricultural indigenous knowledge (AIK) in Uganda, which is useful in livestock keeping, crop management and food processing and storage as well as soil and water management. Unfortunately, this AIK is becoming less visible and irrelevant in some communities because of the adoption of modern methods of farming. In fact, a lot of AIK has remained largely undocumented which threatens its sustained utilisation. One of the bottlenecks of the effective utilisation of AIK is access to relevant and usable indigenous knowledge for the diverse stakeholders in the agricultural sector including farmers. It seems farmers in Uganda are adopting modern methods of agriculture at the expense of the AIK because of the less perceived benefits that AIK promises because crops planted using AIK have often faced pests and diseases and not yielded much. The problem is perhaps compounded because of increasing population growth, land fragmentation as well as migration to urban areas. This phenomenon raises the question of how AIK can be conserved. This paper is based on a study that investigated how Agricultural Indigenous Knowledge (AIK) is documented and disseminated in addition to identifying the challenges faced in its management for sustainable food security in Uganda ' s district of Soroti. Data in this study was collected through interviews, focus group discussions, document reviews and participant observation. The study findings revealed that despite the advent of modern farming methods, many small-scale farmers in the Soroti district continue to embrace indigenous knowledge in farming such as in managing soil fertility, controlling pests and diseases, controlling weeds, soil preparation, planting materials, harvesting and storage of indigenous root crops and animals. The study concludes that indigenous knowledge is still widely used but most of it is not documented nor fully understood by some members of the community; and that the Iteso and Kumam cultures have some restrictions on who acquires the knowledge. Thus the study recommends that AIKs be recorded for posterity, AIK should be researched upon further, be thoroughly documented and made freely available to anyone who needs it. On the whole, AIK in Soroti district requires attitudinal, behavioural, and methodological changes to give it a scientific touch. Moreover, small-scale farmers should be involved in agricultural extension services rather than leaving the work to formally trained officers who may have little attachment to specific cultural practices in the areas they operate.